Prediction of maximal oxygen uptake using the Rockport one mile walk test and rating of perceived exertion - Beauchene, Alexander L. (My University, 2015)
This study was designed to evaluate the effect of using the Rating of Perceived Exertion (RPE) on the accuracy of the Rockport 1- mile walk test. Eighty-eight subjects ranging in age and fitness levels performed a Rockpmt 1- mile walk test and a Balke maximal oxygen consumption (V02max) test on the treadmill. During both tests the subject's RPE was recorded each stage of the V02mnx test and every 200 meters of the Rockpmt test. Maximal oxygen consumption was predicted by using linear regression. The accuracy of the equations was determined using multiple regression (R2 between V02max predicted fiom 1 mile walk time and RPE with measured V02max The Rockport lJ equation was slightly less accurate compared to the original Rockport, but is simpler as it only used 2 variables. The equation: Predicted V02max = 31.142- (1.13- (Walk time))- (.305(final RPE)) x 3.5, R2 predictive power to the equation when compared to only using time to walk !mile and was not significantly different than the original Rockport equation. ) and standard error of estimate (SEE).
Keywords: Exercise -- Physiological aspects; Physical fitness -- Health aspects; Walking -- Resesarch